The complete mitochondrial transcript of the red tail loach Yasuhikotakia modesta as assembled from RNAseq (Teleostei: Botiidae) - Grau, José Horacio; Hilgers, Leon; Altmüller, Janine; Šlechtová, Vendula; Bohlen, Jörg (Mitochondrial DNA. Part B, Resources, 2017)
Here, we present the first complete mitochondrial genome of the Red Tailed Loach Yasuhikotakia modesta (Teleostei: Botiidae) from Thailand, assembled from next-generation transcriptome sequencing data. The assembled transcript corresponds to the full length mitochondrial genome of Y. modesta, which measured 16,865 bp in length, and contained 13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes. A slight A + T bias was observed in the mitogenome of Y. modesta with an overall base composition of 32.2% A, 25.8% T, 26.4% C, and 15.4% G, and a GC content of 41.8%. The gene arrangement was identical to that of previously described loach mitogenomes.
Keywords: mitogenome; loach; Yasuhikotakia modesta; Botiidae